The structure of cybercrime networks: transnational computer fraud in Vietnam - Nguyen, Trong (Journal of crime and justice, 2021)
This study examined a sample of transnational computer fraud cases involving bank card fraud and phone scams investigated by the Vietnamese police between 2010 and 2018. This research used social network analysis to evaluate the relationships between computer fraud suspects. The study combined data from criminal profiles and in-depth interviews with police officials to determine the structural characteristics of sample cases. Results showed that transnational computer fraud in Vietnam occurs online and offline, with primary modus operandi including bank card fraud and phone scams. Moreover, the organizational structures of transnational computer fraud in Vietnam differ from those broadly assumed by scholars. Accordingly, this study proposes that the degree of leadership within cybercriminal networks can be used to construct a new typology with four categories: ‘swarm networks,’ ‘distributed networks,’ ‘single-directed networks,’ and ‘group-directed networks.’ As the first study of this nature conducted in Vietnam, this study contributes to the literature of cybercrime and especially, to the knowledge of transnational computer fraud in Asia and beyond.